Heat transfer and wetting behaviour of falling liquid films in inclined tubes with structured surfaces. (25th March 2022) - Eichinger, S.; Storch, T.; Grab, T.; Tepel, S.; Heinrich, M.; Fieback, T.; Gross, U.
Abstract: This study examines wetting behaviour and evaporation heat transfer of a falling liquid film inside a circular tube carrying grooves at its internal surface. The experiments include five different structures (four helical, one longitudinal) and one smooth tube (Cu, d i ≈ 27 mm ) with counter-current flow of liquid (downwards) and vapour (upwards). Results are obtained for liquid propane films ( P r = 2 . 79, R e smooth tube = 160 − 645 ) at different twisting angles and height of the grooves, tube inclination angles ( β = 0° − 20° from the vertical), mass flow rates (from 5 kg/h up to 20 kg/h) and driving temperature differences (2 K, 3 K and 4 K) mainly at a film inlet temperature of 293.15 K. For wetting behaviour investigations the liquid film is visually observed at the lower end of the tube. The experiments reveal that the internal structures used lead to a strong improvement in both wetting behaviour and heat transfer, even up to inclination angles of 20° . The amount of capillary transported liquid within the grooves coupled with groove geometry itself are the main impacts on wetting behaviour and will be discussed within this paper. Highlights: Helically twisted structures resulting better wetting and heat transfer. Greater groove mass flow rate supportive for greater heat transfer. High aspect ratios supportive for high heat transfer. Driving temperature difference influences wetting and heat transfer. Small inclination with small influence on heat transfer.